SOCIOLOGICAL Sociological Considerations For Islamic Law's Application And Experience In Indonesia - Azis, Azizah; Kurniati, Kurniati; Misbahuddin, Misbahuddin (Cita konsultindo, 2023)
This research intends to examine the social aspects of the implementation and enforcement of Islamic law in Indonesia. This research is qualitative in character and was conducted at a library. The study's findings demonstrate the reciprocal link between Islamic law and patterns of society behavior, with sociology serving as one method of comprehending it. In essence, Indonesian law is based on Islamic principles that evolved and changed as Indonesian society did throughout the course of its history. There are four different schools of thought that may be used to explain how Islamic law is applied in Indonesia: formalistic-legalistic, structuralistic, culturalistic, and sustainable-applicative.